Wasps (Hymenoptera: Chalcidoidea) associated with galls in seed-capsules of Eucalyptus camaldulensis (Myrtaceae) in South Africa : species composition, trophic relationships and effects - Klein, Hildegard (Department of Biological Sciences, 2024)
The Australian river red gum (Eucalyptus camaldulensis Denhardt) (Myrtaceae) is regarded in South Africa as a valuable general-purpose utility and ornamental tree, as well as an essential source of nectar and pollen to sustain the honeybees which are crucial for pollinating the economically important fruit crops in mainly the Western cape Province. Despite its utility value, it is regarded as invasive in South Africa, the major concern being the large amounts of water it consumes when growing along watercourses. River red gum is therefore the subject of conflicts in interests between government agencies that target it for control actions, and farmers and beekeepers who utilize it. As a contribution towards resolving this conflict in interests, a research project was initiated to investigate the potential use of host-specific insects that might reduce the number of viable seeds produced by E. camaldulensis. The aim was to reduce its invasive potential while retaining its general utilizability for all concerned. From the start, the need for introduced agents from Australia was weighed against the presence of two species of chalcidoid wasps, both regarded as gall inducers, in the seed capsules of E. camaldulensis in South Africa. The current study was motivated by the need for information on the biology of these two species and the effect they were having on seed production in their host plant. As it progressed, three more chalcidoid species, all undescribed at that time and probably of Australian origin, were found to be emerging from the seed capsules of E. camaldulensis collected in several parts of South Africa, and these became part of the investigation. The aims of this study were to determine • which species was the gall inducer(s), • the role of each of the other associated hymenopteran species in the gall, • the extent to which these hymenopteran species affected the reproductive potential of E. camaldulensis, and ultimately, • whether this complex of hymenopteran species, or any single speCies, had the potential to reduce the invasive potential of E. camaldulensis in South Africa, and therefore to serve as biocontrol agents in an integrated management plan of Eucalyptusspp. in South Africa. The first chapter is a literature study, which deals with the possible biological role of each of the five chalcidoid species associated with the galls in the seed capsules of trees in the Eucalyptus camaldulensiscomplex. They are: Megastigmus zebrinusGrisseli (Torymidae: m Megastigminae); Quadrastichode/la nova Girault (Eulophidae: Tetrastichinae); Leprosa milga Kim & La Salle (Eulophidae: Tetrastichinae); Aprostocetus sp. (Eulophidae: Tetrastichinae); and another undescribed species (Eulophidae: Tetrastichinae, genus indet.)/ which will be referred to as Eulophid #4 and is characterised by a distinct elongate hypopygium. An account is also given of galls, their development and biology, and of gall inducers and other associated insects, e.g. parasitoids, predators and inquilines. Chapter 2 deals with the geographical distribution of the seed capsule galls of E. camaldulensis in South Africa, and with the hymenopteran species that were reared from the samples collected from various parts of the country and during different periods of the year. It also discusses the emergence patterns of the various hymenopteran gall inhabitants, as observed during a detailed, one-year survey of three test trees in different parts of Pretoria. The emergence patterns of the insects are correlated with the phenology of the test trees, as recorded during the same period. Chapter 3 describes attempts to determine the biological role of each of the five chalcidoid gall inhabitants. This entails the dissection of flowerbuds, flowers and seed capsules of E. camaldulensis, oviposition trials in sleeves on intact trees, and the laboratory observation of adults. In some of the cases it was possible to identify the juveniles that were encountered during dissections by matching DNA sequences of the juveniles and of adults. By following all the available leads, it was concluded that Q. nova is the primary gall inducer, that L. milga probably parasitizes Q. nova, and that M. zebrinus is a parasitoid of either Q. nova or L. milga, but that its larvae also feed on gall tissue. Aprostocetus is possibly a parasitoid of L. milga. The last species (Eulophid #4) was not abundant enough to allow studies of its biology. In the final chapter, an account is given of the effect of galling on seed production in the three E. camaldulensistrees in Pretoria, as an indication of the ability of the gall inducer to reduce the invasiveness of E. camaldulensis in South Africa without compromising its valuable attributes. It was concluded that the presence of galls in the seed capsules significantly reduced the number of viable seeds in the capsule. This seed reduction could be expected to reduce the spread of E. camaldulensis where it grows along watercourses, which is also where it is most invasive. This study has expanded the available knowledge on the trophic relationships of chalcidoid wasps associated with eucalypts by showing that: • the tetrastichine Quadrastichodella nova induces galls in the seed capsules of trees of the Eucalyptus camaldulensiscomplex in South Africa; • the galls develop in the placenta of one of the locules in the seed capsule, and are not modified seeds, or outgrowths from the capsule wall, as previously believed; • galling of the seed capsules reduces the production of viable seeds in £ camaldulensis, • at least three parasitic chalcidoid species are associated with these galls; • of these, the tetrastichine Leprosa milga probably parasitizes the larvae of the gall inducer; • the tetrastichine Aprostocetus is possibly a hyperparasitoid of L milga; • the torymid Megastigmus zebrinus is a parasitoid that also feeds on gall tissue; • several authors referring to M. zebrinus and L milga as gall inducers have been mistaken.